Level of Satisfaction on the Implementation of Performance Appraisal Among Non Academic Staff - Zaharah, Mohamed (2011)
The study was conducted to identify the level of satisfaction among non academic staff of one of the public universities located in Northern Malaysia on the implementation of performance appraisal system. The aims of the study were to: (i) measure the level of satisfaction on the implementation of the performance appraisal system; (ii) to investigate the relationship between independent variables (rater's competency, evaluation process, compliance to rules & standard practices, employees' participation and dependent variable (level of satisfaction); and (iii) to measure the influence of rater's competency, evaluation process, compliance to rules & standard practices and employees' participation on the level of employees' satisfaction on the implementation of the performance appraisal system. Data were gathered through questionnaires distributed to 377 respondents comprising of officers in the category of management and professional, support staff I, and support staff II. However, only 178 questionnaires (47 per cent) that were returned found to be useable for further analysis. The data were analyzed using Statistical Package for Social Sciences (SPSS) software, version 17.0. The level of satisfaction was found to be at medium level, with a mean score of 2.89. All variables showed presence of a positive and significant relationship, with a value of correlation coefficients between 0.291 and 0.386. The value of Adjusted R Square, however, amounted to only 0.141 which indicates that there was only 14.10 per cent change in the level of satisfaction that can be explained by the four (4) independent variables which are rater's competency , evaluation process, compliance to rules & standard practices and employees' participation. The remaining 85.90 per cent was due to other factors which were not considered in this research. Generally, the findings indicate that the level of satisfaction, as measured along the given four independent variables, support the hypothesis that there is positive and significant relationship between' the variables. The findings also show that the organization should focus more on the factors that are linked with employees' satisfaction.